Arene transition metal complexes in synthesis - Mobbs, B; B. E. Mobbs (1985)
﻿ This thesis deals with the applications of organopalladium and organochromium chemistry to the functionalisation of the benzopyran ring system, at a variety of oxidation levels. Section I demonstrates the functionalisation of 3-, 6-, and 8-bromochromones via palladium (0) insertion into the C-Br bond. The resultant arylpalladium species are shown to undergo addition to the least substituted end of a variety of olefins including methyl acrylate, acrylonitrile and styrene. Subsequent palladium-hydride elimination leads to overall palladium catalysed vinylation of the chromone and the synthesis of a number of novel compounds. Vinylation occurs regiospecifically at the site of chromone bromination and is shown to allow clean substituent introduction into each of the three sites. The palladium catalysed reaction of 3,6-dibromo-chromone with methyl acrylate leads to vinylation at both the C3 and C6 positions. Carbonylation of the 6-bromochromone in ethanol or butanol leads to the 6-ethyl or 6-butyl esters respectively. The palladium catalysed vinylation of the 6-bromochromone with ethyl vinyl ether leads to a mixture of products from addition of the chromone to either end of the olefin. With p-bromophenol or p-bromo-N,N-dimethylaniline the reaction gives exclusively the acetylated product arising from addition to the more substituted end of the olefin. This change in orientation is rationalised by considering the polarisation of the olefin and the arylpalladium species. Section II demonstrates the functionalisation of chroman and 4-chromanol via coordination to the Cr(CO)3 moiety. (η6-Chroman)Cr(CO)3 is synthesised and is shown to undergo regiospecific ring deprotonation at C8 under kinetic conditions or regiospecific benzylic deprotonation at C4 under thermodynamic conditions. The resultant anions are quenched with alkyl halides, aldehydes, Eschenmoser's salt and methyl disulphide resulting in selective functionalisation of either site. No mixed products are observed. The uncomplexed arene is shown to be totally unreactive under identical conditions. (η6-4-Chromanol)Cr(CO)3 is synthesised and is shown to undergo regiospecific C8 ring deprotonation by comparison with authentic samples of the C5 and C8 methylated alcohols. Protection of the hydroxyl group as its methyl, t-butyldimethylsilyl or methoxymethyl ethers is found not to alter the regiochemistry of deprotonation. The 4-chromanol t-butyldimethylsilyl and tri-i-propylsilyl ethers are synthesised and coordinated to the metal unit. Cleavage of the silyl ethers is shown to proceed with loss of stereochemistry, indicating C-0 bond cleavage.